Survey on User Group Revocation and Integrity Auditing of Shared Data in Cloud Environment - Rai, Rohit; Singh, Upasna (International Journal of Computer Sciences and Engineering, 2018)
The term ‘group Signature’ is inherited element of ‘digital signature’ that permits any group members to sign the messages on behalf of its group which they belongs too. The identity of original signer is hidden by this resulting signature. Subsequently, the identity of the original signer can be reveal by the group manager, who is only responsible to, open the signatures respectively. The efficient approach that combines the revocation mechanism into group signature schemes based on the robust RSA assumption. The security is an essential factor for a secure group signature scheme, and the third party introduction make the scheme more practical and simple than the previous schemes of this kind.